Gambaran Karakteristik Akseptor Keluarga Berencana (KB) Metode Kontrasepsi Jangka Panjang (MKJP) di Desa Payaman - Putri Yunia Fitri; Nurul Fitriyah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2017)
Indonesia have a problem on the number one of quality human resources with the high birth rate each year. In these improvements, it is necessary to increase the degree of life with development and Family Planning (FP). The purpose of this study was to determine description of characteristic FP MKJP acceptors in Payaman village, Ngraho, Bojonegoro. This research was descriptive analytic with quantitative approach. The data were collected using structured questioners to 243 mothers and 213 fathers in Payaman village. The variable that used in this study was age, education, job, hospital sheet, type of contraseption tools and time used contraseption tools. The data were analyzed using descriptive statistic analysis. The result of this study was determine that mayority of populations in Payaman Village, Ngraho Subdistrict, Bojonegoro City has follow FP’s  program.  The description of characteristic FP acceptors that use MKJP method in Payaman Village, Ngraho Subdistrict, Bojonegoro City were 15–45 years old (61%), has job as a farmer (78%), has a low education (66%) An  using IUD as contraseption tools with using period more than 6 years (90%). From this explanation the result of the variable shows that there is no differences risks between FP MKJP and non MKJP.